Pharmacokinetics, Tissue Distribution, and Excretion Characteristics of a Radix Polygoni Multiflori Extract in Rats - Cheng, Wenhao; Wu, Siyang; Yuan, Zheng; Hu, Weiyu; Yu, Xin; Kang, Nianxin; Wang, Qiutao; Zhu, Mingying; Xia, Kexin; Yang, Wei; Kang, Chen; Zhang, Shuofeng; et al. (Frontiers in Pharmacology, 2022)
Despite the progress in pharmacological activity and toxicity of Radix Polygoni Multiflori (RPM), the material basis of its toxicity is still unclear. Here we aimed to perform a multi-compound pharmacokinetic analysis and investigate the characteristics of tissue distribution and excretion of RPM components after oral administration to rats. The findings demonstrated that the active ingredients of RPM extract were quickly absorbed after oral administration, wherein the exposures of emodin, 2,3,5,4'-teterahydroxystilbene-2-O-β-D-glucoside (TSG), citreorosein, torachrysone-8-O-glucoside (TG), emodin-8-O-β-D-glucoside (EG), and physcion-8-O-β-D-glucoside (PG) were high in the body. The tissue distribution of emodin, TSG, TG, EG, and PG were high in the liver and kidney. These components were the key contributors of the effectivity and toxicity of RPM on the liver and kidney. Most of the active ingredients were mainly excreted through fecal and bile excretion, while a few were converted into other products in the body and excreted through urine and feces.